Peasant Colonization, Identity and Community Agreements: The Yellow Line as an Experience of Forest Protection - Quijano Mejía, Claudia; Alfonso León, Daniel (Universidad del Rosario, 2020)
The focus of discussion in this article is the process of construction and mobilization of the peasant identity in the valley of the Cimitarra river through the creation of community initiatives to protect the environment, specifically, the so-called Yellow Line: a vast stripe of primary forest south to the San Lucas mountain range, protected by peasants through the establishment of community agreements that prohibit productive or extractive activities within the area. The study is qualitative, with a focus on historical memory, based on the voice of the protagonists: peasant settlers who promote the initiative. The article discusses how, through the experiences shared during the process of colonization of the region and the establishment of community agreements, a self is created and recreated that allows the dialogue with local and national entities and authorities.